The effect of specific background electrolytes on water structure and solute hydration: Consequences for crystal dissolution and growth - Kowacz, M.; Putnis, Andrew (Pergamon, 2008)
Barium sulfate is used as a model system to illustrate how solution composition can affect processes of crystal dissolution and growth. Rates and modes of reactions as well as morphological features can be modified by the introduction of simple ionic salts (KCl, NaCl, LiCl, CsCl, NaF, NaNO3), due to the effects of these electrolytes on water structure dynamics and solute hydration. Based on the results of AFM in situ experiments performed at supersaturation (O) = 10.6 ± 0.1 and ionic strength (IS) in the range of 0.005-0.1 M we show that growth and dissolution behavior of barite changes under conditions of constant thermodynamic driving force (O) and constant IS in a systematic way depending on the specific background electrolyte used to adjust IS. The results are interpreted in terms of the relationships between solution composition, ion properties and the consequent growth and dissolution behavior. Island spreading rate is affected by salt-specific effects on the activation energy barrier of expelling water molecules from solvation shells of barite building units. Dissolution kinetics depends on the balance between the energy expended on breaking solvent structure and the energy gain on hydrating Ba2+ and SO42 - ions, which are specific for different electrolyte solutions. Nucleation rates are determined by the frequency of water exchange around a barium cation which also depends on solution composition. Relating the structure of the solution to its composition can help to understand phenomena such as growth and dissolution in the presence of organic additives or impurity incorporation. © 2008 Elsevier Ltd. All rights reserved.